ECB asset purchase programs raise inflation expectations in the Euro area - Malte Rieth; Lisa Gehrt (DIW Economic Bulletin, 2016)
Facing deflationary threats, the ECB has engaged in several forms of asset purchase programs to fulfill its mandate of maintaining price stability. A main objective of these programs is raising inflation expectations, as these are a main determinant of actual inflation. This study empirically evaluates the effectiveness of these ECB policies in raisinginflation expectations. The results suggest that the ECB announcements of asset purchase programs significantly increased the expected inflation in the euro area, albeit to a quantitatively modest extent. All in all, inflation expectations were raised by 20 to 30 basis points.
Keywords: E52; E31; E58; 330; monetary policy; transmission; euro area; regression analysis